Sperm storage in Neotropical snakes: a spermatozoon physiological and ultrastructural approach - Coeti, Rafaela Zani (2020)
The sperm storage in vertebrate females is a well described process and occurs for distinct time periods, taking place in different portions of female reproductive tract. Among all vertebrates, the reptile females are known for the longer sperm storage and in snakes there are reports of up to 5 years, occurring inside the anterior vagina, posterior uterine tube and infundibulum, whether in crypts or in SST. In addition, male snakes can also store sperm for at least one season, inside the ductus deferens. However, since the first sperm storage description in snakes, until works reporting the estimated storage time and within-clutch multiple paternity, the same question stills without answer: How is possible that the spermatozoa be alive for so long? There are hypothesis indicating that female oviduct is in charged for sperm maintenance, others suggest that sperm cells maintenance are due to sexual segment of kidney (SSK) secretions, but few studies focus on how the spermatozoon structure and physiology could be the key for its long survival. Thus, this work aimed to analyse the Neotropical snakes spermatozoa with a physiological and ultrastructural approach, for the purpose of evaluating and describing mature sperm before copulation. Therefore, we divided our study on four topics: (1) establishing a minimally invasive snake semen collection protocol; (2) evaluation of the snake semen parameters motility, vigor and vitality; (3) description the spermatozoa ultrastructure and (4) recognize if the genetic material of mature snake sperm is viable.